Primary Squamous Cell Carcinomas Arising in Intracranial Epidermoid Cysts: A Series of Nine Cases and Systematic Review - Zuo, Pengcheng; Sun, Tao; Wang, Yi; Geng, Yibo; Zhang, Peng; Wu, Zhen; Zhang, Junting; Zhang, Liwei (Frontiers in Oncology, 2021)
Abstract Objective: Primary squamous cell carcinomas (PSCCs) arising in intracranial epidermoid cysts (IECs) are very rare, and their management remains unclear. The authors aimed to enunciate the clinical features and design a treatment protocol based on reported cases combined of ours. Methods: The clinicoradiological data were obtained from 9 patients with PSCCs arising in IECs, who underwent surgical treatment in Beijing Tiantan Hospital between July 2012 and June 2018. We also searched the PubMed databases using the keywords “epidermoid cyst” and “malignant”, “malignancy”, “intracranial”, “brain”, “squamous cell carcinoma” from 1960 to 2020 and 45 cases were collected. Risk factors for overall survival (OS) were evaluated based on reported cases combined of ours. Results: Our cohort, mean age 51.2±8.3 years (ranging from 39 to 61 years), included 8 males and 1 female. Among them, 4 patients had a surgical history, and the pathological results were benign epidermoid cysts (ECs). The other patients did not have a surgical history, and were considered natural malignant transformation of IECs because of benign ECs and squamous cell carcinomas (SCCs) coexisting in the lesion, and they fulfilled Garcia criteria. Gross total resection (GTR) was achieved in 3 patients, while non-gross resection (non-GTR) was achieved in 6 patients. Radiotherapy was administered to 5 patients, respectively. After a median follow-up of 16.7±21.6 months (ranging from 3 to 72 months), 8 patients died with mean overall survival of 9.75±6.6 months (ranging from 3 to 23 months). In the literature between 1965 and 2020, 45 cases of PSCCs arising in IECs were identified in 23 males and 22 females with a mean age of 55.2±12.4 years. A multivariate analysis demonstrated that postoperative radiotherapy (p=0.002) was the only factor that favored OS. Conclusion: Malignant transformation of intracranial epidermoid cysts was prevalent in elderly patients with slight male predominance. GTR of previous benign IECs is recommended. For remnant benign IECs, close follow-up should be performed. Postoperative radiotherapy for PSCCs could bring survival benefit. GTR of these malignant intracranial tumors is difficult when they involve important brain structures. Future studies with larger cohorts are necessary to verify our findings.